2019
DOI: 10.1016/j.jmb.2019.01.032
|View full text |Cite
|
Sign up to set email alerts
|

The Role of SurA PPIase Domains in Preventing Aggregation of the Outer-Membrane Proteins tOmpA and OmpT

Abstract: • The role(s) of the two PPIase domains in E. coli SurA remain unresolved • Multiple SurA PPIase domains are conserved in βand γ-proteobacteria • OMP sequence properties do not reveal a correlation with SurA domain architecture • tOmpA and OmpT require different SurA domains for chaperoning • SurA-OMP specificity suggests one reason for multiple PPIase domain conservation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 91 publications
(131 reference statements)
8
48
0
Order By: Relevance
“…In the presence of OmpX, regions in SurA that are protected from deuterium uptake upon substrate binding cluster to the core domain. No change in protection in P2 was detected in the presence of OmpX, consistent with the tag transfer XL-MS results and with previous results which have shown that P2 is not required to prevent the aggregation of the small (8-stranded) OmpA 28 . Intriguingly, two regions of SurA (residues 46-72 in the N-terminal region and 212-239 in P1) ( Fig.…”
Section: Conformational Changes In Sura Upon Omp Bindingsupporting
confidence: 92%
See 3 more Smart Citations
“…In the presence of OmpX, regions in SurA that are protected from deuterium uptake upon substrate binding cluster to the core domain. No change in protection in P2 was detected in the presence of OmpX, consistent with the tag transfer XL-MS results and with previous results which have shown that P2 is not required to prevent the aggregation of the small (8-stranded) OmpA 28 . Intriguingly, two regions of SurA (residues 46-72 in the N-terminal region and 212-239 in P1) ( Fig.…”
Section: Conformational Changes In Sura Upon Omp Bindingsupporting
confidence: 92%
“…SurA binds unfolded OmpX with low affinity (K d,app of ~800 nM), as measured by microscale thermophoresis (MST) ( Supplementary Fig. 8), similar to the affinity of SurA for other OMPs 28,43,44 . SurA-OmpX complexes were assembled by rapid dilution of urea-denatured OmpX into a solution of SurA (final concentrations: 5 µM OmpX, 5 µM SurA, 0.24 M urea) (see Methods) immediately prior to crosslinking with DSBU.…”
Section: Sura Binds Its Omp Substrates At Multiple Interaction Sitesmentioning
confidence: 59%
See 2 more Smart Citations
“…BAM and BAM(∆BamB) was over-produced in E. coli C43 according to established protocols (Iadanza et al, 2016;Roman-Hernandez et al, 2014). For preparation of SurA and SurA-OmpA complexes, both proteins were over-produced separately in 1 L of cultures as described previously (Humes et al, 2019). Both were harvested by centrifugation, lysed in a cell disruptor…”
Section: Protein Production and Purificationmentioning
confidence: 99%